2019
DOI: 10.1186/s13048-019-0496-2
|View full text |Cite
|
Sign up to set email alerts
|

The ovarian germinal reserve and apoptosis-related proteins in the infant and adolescent human ovary

Abstract: BackgroundNormal pubertal ovary displays all stages of follicular development and a biased BAX/BCL2 protein ratio in favor of pro-apoptotic BAX protein comparable to the adult ovary. However, adolescents suffering malignant extra-gonadal disease show a limited follicle development after cytotoxic drug treatment and a reduced capacity of in vitro follicle growth. We evaluated the expression of pro- and anti-apoptotic members of the BCL2 gene family, the FAS/FAS-L proteins from the extrinsic apoptosis pathway, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…This study was expanded upon by Omari et al (2015), who observed these same effects in vivo as a result of germ cell‐specific depletion of MCL1. Intriguingly, expression of BCL2 and BAX proteins has been observed during adolescent human folliculogenesis as well, though their functions in this context remain unclear (Albamonte, Albamonte, Bou‐Khair, Zuccardi, & Vitullo, 2019; Albamonte, Albamonte, Stella, Zuccardi, & Vitullo, 2013). These data highlight that many BCL2‐family members may exert their functions during specific developmental windows despite their more ubiquitous expression, emphasizing that it may be the net balance of all family members expressed during a particular developmental process that regulates cell survival outcome.…”
Section: Diverse Cell Death Pathways Facilitate Primordial Follicle Amentioning
confidence: 99%
“…This study was expanded upon by Omari et al (2015), who observed these same effects in vivo as a result of germ cell‐specific depletion of MCL1. Intriguingly, expression of BCL2 and BAX proteins has been observed during adolescent human folliculogenesis as well, though their functions in this context remain unclear (Albamonte, Albamonte, Bou‐Khair, Zuccardi, & Vitullo, 2019; Albamonte, Albamonte, Stella, Zuccardi, & Vitullo, 2013). These data highlight that many BCL2‐family members may exert their functions during specific developmental windows despite their more ubiquitous expression, emphasizing that it may be the net balance of all family members expressed during a particular developmental process that regulates cell survival outcome.…”
Section: Diverse Cell Death Pathways Facilitate Primordial Follicle Amentioning
confidence: 99%
“…BAX as a proapoptotic protein is expressed in both granulosa cells and oocytes. It is an important regulator of follicular growth and atresia, which plays a central role in ovarian cell death by the intrinsic pathway of apoptosis (17,18). A higher incidence of apoptosis was shown within grafted ovarian tissue (19)(20)(21)(22); however, a well-preserved ovarian follicles with a low proportion of cell death in grafted tissue was demonstrated by others (23).…”
Section: Introductionmentioning
confidence: 98%
“…Apoptosis cell death plays a fundamental role in follicular atresia. It takes place by two intrinsic and extrinsic pathways, and several pro-and antiapoptotic proteins involve in these pathways (17). BAX as a proapoptotic protein is expressed in both granulosa cells and oocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The number of primordial germ cells, or oogonia, peaks at approximately 6–7 million during mid-gestation, followed by progressive atresia with approximately 1–2 million oocytes present at birth ( Motta et al, 1997 ; Pereda et al, 2006 ; Mamsen et al, 2012 ). By puberty, there is estimated to be 300,000–500,000 oocytes remaining, and approximately 25,000 at age 37 years ( Forabosco and Sforza, 2007 ; Albamonte et al, 2019 ). Menopause occurs when the number of remaining oocytes falls below a critical threshold of about 1000, regardless of age ( American College of Obstetricians and Gynecologists Committee on Gynecologic Practice and Practice Committee, 2014 ).…”
Section: Introductionmentioning
confidence: 99%